Factors Associated Between Food Consumption Patterns and Nutritional Status of Toddlers Aged 3-5 Years in Tarus Health Center, Kupang Regency - Bora, Sarniati; Aspatria, Utma; Laga Nur, Marselinus (Faculty of Public Health, Nusa Cendana University, 2022)
According to data from the Tarus Health Center in 2021, 47 toddlers under five are malnourished, 170 toddlers are malnourished, 57 toddlers are at risk of overnutrition, 20 toddlers are malnourished, and four are obese. This study aims to determine the relationship between food consumption patterns and the nutritional status of children aged 3-5 years at the Tarus Public Health Center, Kupang Regency. An across-sectional research design was used in the form of an analytic observational study. The population in this study were all children aged 3-5 years who were in the Work Area of ​​the Tarus Health Center as many as 419 toddlers. The research sample amounted to 100 people. The sampling technique in this study using the proportional stratification random sampling technique is a sampling process by dividing the population into strata, selecting random samples from each stratum, and combining them to estimate population parameters. A Chi-Square test was performed to analyze the data. The findings showed that the type of food (p = 0.000), energy adequacy (p = 0.034), and protein adequacy (p = 0.011) were all related to the nutritional status of children under five. While the frequency of unhealthy eating is not related to nutritional status (p = 0.090), it is recommended that health workers carry out more nutrition-aware family counseling, especially to parents whose toddlers have low, less, or more nutritional status, so that nutritional status can be managed effectively